Interdisciplinary and Multidisciplinary Islamic Studies: Toward an Integratif and Interconnected Epistemology of Knowledge - Harahap, Efridawati; Nasution, Abdul Riswan; Damanik, Agustina (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2025)
Islam represents a syamil and holistic religious tradition that embeds knowledge at the core of its civilizational vision, as reflected in the primordial command of iqra’. Historically, during the Islamic Golden Age, religious and scientific disciplines evolved within an integrated epistemic framework, demonstrated by the works of Muslim polymaths who refused the dichotomy between ulum al-din and ulum al-dunya. The rise of Western colonialism and secular educational reforms, however, generated a structural epistemological rupture that separated religious knowledge from modern science. In the Indonesian context, this fragmentation surfaced in the divergence between pesantren/madrasah and public schools, producing generations with partial disciplinary competence. Contemporary Muslim thinkers including Ismail Raji al-Faruqi, Syed Muhammad Naquib al-Attas, and Fazlur Rahman have formulated intellectual responses to reconstruct Islamic epistemology, subsequently institutionalized through integrative–interconnective paradigms in Islamic higher education. In the era of globalization and the Fourth Industrial Revolution, the reintegration of knowledge is increasingly indispensable to ensure that scientific advancement remains ethically grounded and that Islamic studies retain analytical relevance to complex socio-civilizational challenges. This article asserts that adopting an integrative paradigm of knowledge is essential for addressing the epistemological crisis in the Muslim world and reaffirming Islam’s transformative role in modern civilization.